Penerapan model pembelajaran kooperatif tipe two stay-two stray (ts-ts) untuk meningkatkan keterampilan pemecahan masalah bangun datar pada peserta didik sekolah dasar - Ayu Fitriani Nurjanah; Riyadi Riyadi; Sadiman Sadiman (Didaktika Dwija Indria, 2019)
Research this aiming for increase problem solving skills two dimentional figure with model TS-TS and for know the application of model TS-TS on the problem solving skills two dimentional figure. Classroom Action Research was a type of this research, carried out for 2 cycle with 4 activities.Technique of collection data carried out were with test, debriefing, observation and documentation. Technique of validity data using triangulation of source and triangulation of technique . Technique of analysis data used were descriptive statistics, descriptive of comparative and interactive analysis. Results research to show average of class on pre-action is 48,44 and completeness is 7,14% , increase on cycle I with average of class 69,97 and completeness classical 53,85% and increase again on cycle II with average of class reaching 81,84 and completeness is 85,71%. Based on results research, can be know that implementation Cooperative learning model type Two Stay - Two Stray (TS-TS) can increase problem solving skills two dimentional figure on students of fourth A grade in state elementary school of 01 Nangsri academic year 2018/2019.Keywords: Cooperative learning model, Two Stay - Two Stray (TS-TS), problem solving skills, two dimentional figure